Superparamagnetic-to-Diamagnetic Transition in Hydroxo-Bridged Trinuclear Copper(II) Complex Nanorods - Giri, S; Saha, S. K (Journal of physical chemistry. C, 2010)
Although magnetic interaction in trinuclear Cu(II) complex is a widely studied subject, the field remains totally unexplored in their nanophase. Here, single crystalline nanorods of hydroxo-bridged trinuclear Cu complex with partial cubane (Cu3O4) core ([Cu3(μ3-OH)(SE)3](ClO4)2·0.5H2O, SE being the condensed form of N,N-dimethylethylenediamine and salicylaldehyde) is synthesized in the nanochannel of anodic alumina template. Considering the spin Hamiltonian for a trinuclear system, the magnetic exchange interaction shows a weak intramolecular antiferromagnetic interaction (J= −2 cm−1) and a weak intermolecular ferromagnetic interaction (zj′ = 0.72 cm−1). At 2 K, both bulk as well as nanorod samples exhibit superparamagnetic behavior with domain size 1.5 nm; however, at higher temperature, remarkable changes in magnetic properties such as field induced diamagnetic transition are noticed for nanorods. Due to directional growth of nanorods along the c-axis (nanochannel axis), out of two types of hydrogen bonds only that acting along the c-axis with a donor−acceptor distance of 3.094 Å is more effective in the magnetic field. These effects of giant diamagnetism in crystalline nanorods are attributed to the charge delocalization across the H-bonds acting along the c-axis.